2019
DOI: 10.3390/su11215885
|View full text |Cite
|
Sign up to set email alerts
|

Runoff Predicting and Variation Analysis in Upper Ganjiang Basin under Projected Climate Changes

Abstract: Catchment runoff is significantly affected by climate condition changes. Predicting the runoff and analyzing its variations under future climates play a vital role in water security, water resource management, and the sustainable development of the catchment. In traditional hydrological modeling, fixed model parameters are usually used to transfer the global climate models (GCMs) to runoff, while the hydrologic model parameters may be time-varying. It is more appropriate to use the time-variant parameter for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The variations of the projected multi-year mean precipitation and temperature over the UGRB during the period 2021-2050 are relatively close to the conclusions proposed by Deng & Wang (2019), and both are precipitation declines and potential evaporation increases; however, in terms of annual runoff, the opposite conclusions are drawn. In this paper, the annual mean runoff is expected to increase by 8.4, 6.5 and 5.0% under three RCPs in the next 30 years, while the latter reported that a decreasing trend about À9.9, À19.5 and À11.4%.…”
Section: Discussionsupporting
confidence: 76%
“…The variations of the projected multi-year mean precipitation and temperature over the UGRB during the period 2021-2050 are relatively close to the conclusions proposed by Deng & Wang (2019), and both are precipitation declines and potential evaporation increases; however, in terms of annual runoff, the opposite conclusions are drawn. In this paper, the annual mean runoff is expected to increase by 8.4, 6.5 and 5.0% under three RCPs in the next 30 years, while the latter reported that a decreasing trend about À9.9, À19.5 and À11.4%.…”
Section: Discussionsupporting
confidence: 76%
“…Annual streamflow prediction is equally important for reservoir operation and water resource management in the Ganjiang River Basin, because it is the prerequisite and foundation for compiling a water resource allocation plan and carrying out reservoir operation. As an important control station in the upper reaches of the Ganjiang River Basin and a runoff monitoring station at the dam site of the Wan'an Reservoir, the Dongbei Hydrological Station is the basin outlet of the study area, controlling a drainage area of 40,231 km 2 [39]. Influenced by the plum rain, rainfall of the Dongbei Hydrological Station concentrates from March to June, accounting for about 54% of annual rainfall.…”
Section: Study Areamentioning
confidence: 99%
“…It overcomes the problem of long-term dependencies and is more suitable for dealing with time series forecasting problems. The computation process of the LSTM unit is described in Equations ( 4)- (8):…”
Section: Long Short-term Memory Networkmentioning
confidence: 99%
“…Currently, runoff prediction models can be divided into two types: process-driven models [8][9][10] and data-driven models [11][12][13]. Process-driven models are modeled to simulate complex non-linear physical hydrological process through a series of mathematical equations based on an understanding and simplification of the principles of the natural water system [14,15].…”
Section: Introductionmentioning
confidence: 99%